Design and Characteristics of Contactless Small-magnetic-metal Detector Base on Tunnel Magnetoresistance Sensors in Differential Circuit - Thanh, Pham Van; Lien, Truong Thi Ngoc; Nam, Luyen Van (VNU Journal of Science: Mathematics - Physics; Vol 40 No 2DO - 10.25073/2588-1124/vnumap.4909, 2024)
Unexpected metal pieces are significant problems for food and pharmaceutical manufacturers. Commonly, c onventional coil metal detectors are used to detect these metal pieces. However, these detectors can only detect cm-size metal pieces, making it challenging to detect mm-size metal pieces. This work presents an advanced contactless small-magnetic-metal detector based on tunnel magnetoresistance sensors (TMR). To improve the system's sensitivity, the differential circuit combined with a simple AC-bias lock-in amplifier was designed to reduce the noise of TMR sensors. The sensitivity of this designed detection system is of 0.44 V/mm with a good linearity of R 2 =0.82674. The experimental results demonstrate that the fabricated prototype sensors can detect metal wires with a size of 100 μm in diameter and 1 mm in length. Due to a high sensitivity and a low-cost of fabrication, this system is promising to apply on the manufacturing lines for detecting unexpected tiny metal pieces.